Exploring agency, knowledge and power in an Australian bulk cereal supply chain: A case study. Issue 4 (3rd June 2014) - Byrne, Romona; Power, Damien
Abstract : Purpose: – The purpose of this paper is to explore how information sharing practices influenced inter-firm relationships. This was done specifically in relation to bulk commodity supply chains, due to the pre-existing power asymmetries in the system. Design/methodology/approach: – This research was conducted using an interpretivist, inductive approach. The intention was to gather a wide range of data and then explore the data to see which themes emerged, rather than focusing on collecting data relevant only to specific themes. Findings: – The key findings of this research focused around the difference between creating situations of compliance or collaboration in a supply chain context. This suggests that by understanding the relationships that exist between organisations, those in procurement and supply chain management roles will be able to better understand and manage the nuances of their supplier relationships. Research limitations/implications: – The study is focused on a supply network specifically configured to facilitate sourcing and distribution of bulk grain. As such the findings need to be understood within the constraints of this context. Practical implications: – Reliance on coercive power in an institutional change process is shown in our study to create a situation of compliance rather than of collaboration. Reliance on a different type of power, such as referent power, would be more successful in creating a situation of collaboration. Social implications: – The sourcing and distribution of bulk grain is fundamental to food distribution in a developed economy. Our study provides a set of propositions indicating where managers can focus to more effectively manage these flows. Originality/value: – The definition of the "agent" also provided an interesting point of comparison. This research found that the ultimate definition of the "agent" changes and can be linked to the institutional differences in ownership within a supply chain. This suggests the potential to redefine the way that Agency theory is discussed. The notion that the "agent" is dynamic and is likely to be the "agent", "caretaker" and more at the same time suggests the potential for the traditional definition of the agent to be challenged.